Post-Structuralist Critiques of Authorship in Generative Artificial Intelligence (AI) Literature - Philip Abayomi Olorunfemi (Inovasi Analisis Data, 2025)
Purpose — This study examines how Generative Artificial Intelligence (GenAI) literature challenges and extends post-structuralist critiques of authorship. It explores how AI-generated texts affect traditional concepts of creativity, originality, intentionality, and authorial authority, and provides a conceptual framework linking post-structuralist theory to algorithmic literary production. Design/methodology/approach — The study employs a qualitative-interpretive and conceptual research design. It involves critical analysis and theoretical synthesis of post-structuralist concepts, including Barthes’ “Death of the Author,” Foucault’s “author-function,” Kristeva’s intertextuality, and Wimsatt and Beardsley’s intentional fallacy, applied to AI-generated literature. Findings — Findings indicate that GenAI destabilizes conventional notions of authorship, redistributing creative agency across programmers, algorithms, datasets, corporate platforms, users, and readers. The role of readers is strengthened as active meaning-makers, especially in contexts where authorial intention is absent or unstable. AI-generated literature thus functions as a contemporary materialization of post-structuralist ideas. Research limitations/implications — The study is theoretical and conceptual; empirical validation through user studies, case analyses, or comparative corpora would strengthen generalizability and practical applicability. Practical implications — Insights from this study inform literary theory, digital humanities, and AI studies, guiding scholars in critically analyzing authorship, intertextuality, and distributed creativity in algorithmically mediated texts. Originality/value — This study contributes a contemporary conceptual framework demonstrating how AI-generated literature operationalizes post-structuralist critiques of authorship and redefines reader and institutional roles in textual production.